Tìm x biết x+48:12= 43
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) 1 < x < 10 3 = > x ∈ {2;3}
b) 2 5 < x ≤ 23 6 = > x ∈ {1;2;3}
a, x - 1 2 = 36
ó x - 1 2 = 6 2
ó x – 1 = 6
ó x = 7
Vậy x = 7
b, 7 x - 11 3 = 2 5 . 5 2 + 200
=> 7 x - 11 3 = 800 + 200
=> 7 x - 11 3 = 1000
=> 7 x - 11 3 = 10 3
=> 7x – 11 = 10
=> 7x = 21
=> x = 3
Vậy x = 3
c, x 11 = x
=> x 11 - x = 0
=> x ( x 10 - 1 ) = 0
=>
d, x 2 = 2 3 + 3 2 + 4 3
=> x 2 = 81
=> x = 9
e, 2 x 3 3 2 = 48
=> 2 x 3 9 = 48
=> 2 x 3 = 48 . 9
=> x 3 = 216
=> x 3 = 6 3
=> x = 6
f, 2 x + 1 3 = 125
=> 2 x + 1 3 = 5 3
=> 2x + 1 = 5
=> 2x = 4
=> x = 2
Đáp án cần chọn là: B
x–43=(35−x)−48
x–43=35–x−48
x+x=35–48+43
2x=30
x=15
a, x - 43 = ( 35 - x ) - 48
\(x-43=35-x-48\)
\(x+x=35-48+43\)
\(2x=30\)
\(x=15\)
b, 305 - x + 14 = 48 + ( x - 23 )
\(305-x+14=48+x-23\)
\(-x-x=48-23-14-305\)
\(-2x=-294\)
\(x=147\)
c, ( x - 6 + 85 ) = ( x + 51 ) - 54
\(x-6+85=x+51-54\)
\(x-x=51-54-85+6\)
\(0=-82\)
\(x\in\varnothing\)
d, -( 35 - x ) - ( 37 - x ) = 33 - x
\(-35+x-37+x=33-x\)
\(x+x+x=33+37+35\)
\(3x=105\)
\(x=35\)
e, - 12. ( x - 5 ) + 7 . ( 3 - x ) = 5
\(-12x+60+21-7x=5\)
\(-12x-7x=5-21-60\)
\(-19x=-76\)
\(x=4\)
f, 30. ( x+ 2 ) - 6 . ( x - 5 ) - 24 = 100
\(30x+60-6x+30-24=100\)
\(30x-6x=100+24-30-60\)
\(24x=34\)
\(x=\frac{17}{12}\)
chúc bạn học tốt
Ta có: \(\frac{7}{9}+\frac{16}{48}=\frac{10}{9}=1\frac{1}{9}\)
\(\frac{43}{8}-0,125=\frac{43}{8}-\frac{1}{8}=\frac{21}{4}=5\frac{1}{4}\)
Vì: \(1\frac{1}{9}< 2< 3< 4< 5< 5\frac{1}{4}\)
=> x= { 2;3;4;5}
\(x-43=35-x-48\)
\(x+x=43+35-48=30\)
2.x=30=> x=15
2) -x+6-85=x+51-54
-x-79=x-3
2x=76=> x=38
3)\(\orbr{\begin{cases}-7-x-3=-3\Rightarrow x=-7\\-7-x-3=3\Rightarrow x=-13\end{cases}}\)
a ) x = 43 30 x = − 43 30 ; b ) x = 3 2 x = 7 6 . c ) x = 13 6 x = 1 2
d ) x = − 94 45 x = 164 45 ; e ) x = 7 8 x = − 3 8 . f ) x = 7 8 x = − 3 8